Organizational culture and its effect on organizational innovativeness in Malaysian higher education institution - Hafit, Nor Intan Adha; Asmuni, Azizan; Idris, Khairuddin; Abdul Wahat, Nor Wahiza (International Academic Research, 2015)
The natural selection of today’s higher education Institutions (HEI) depends on how these institutions adapt to change, better practices and competitiveness. One important area these organisations need to pay attention to is organizational culture, which can create a supportive environment where innovation can flourish and be competitive. Thus, this work proposes to look into the relationship between organizational culture and organizational innovativeness. A scientific research gap has been searched, through an intensive assessment of a previous study, in the literature on the relationship between organizational culture and organizational innovativeness. Afterwards, based on dynamic capabilities theory, this work seeks to fill gap between constructs for competitive advantage. A conceptual framework has been aimed in this research field, as considerably as a contribution towards the enhancement of the related literature.